“I am serious. And don’t call me Shirley.” Internet memes as a medium of propagation of unconventional phraseological replies - Matej Meterc (Lexis: Journal in English Lexicology)
Unconventional phraseological replies such as No, I’m expensive in response to the question Are you free? are a subtype of phraseological replies. Such phraseological replies are an inappropriate, usually humorous or absurd, response to a statement (the stimulus). So far, no extensive research on this type of expression has been found for Germanic and Romance languages with the exception of Norrick [1984, 1993, 2007] and a few English examples mentioned by Čermák [2007: 433] in the English chapter of his monograph. Humorous phraseological replies have been most systematically studied by Bondarenko [2009], who has also presented a dictionary of such expressions in Russian [Bondarenko 2013]. This type of phraseme has been called a humorous answer [Permyakov 1988: 89], intersubjective phraseme (Čermák [2007: 441]), answer formula (Dobrovol’skiy & Baranov [2003]), and dialogue idiom (Khairov [2019]). The use of these kinds of phrasemes is characteristic above all of private communication and spoken language (Dobrovol’skiy & Baranov [2003: 39-40]; Bondarenko [2009: 644]; Meterc & Pallay [2019: 171]). This makes it all the more important to carefully study the (relatively rare) examples of their use in written communication, which includes internet memes. The article analyzes the example of Leslie Nielson’s line “I am serious. And don’t call me Shirley”, which was originally a quote from the film Airplane! [1980]. The coinage of this unconventional phraseological reply is placed in the context of the particular manner in which the many gags in this film were created, described by the directors in an interview. The mechanisms for generating some of the gags in this film are compared with the typical mechanisms for establishing a link between the stimulus and the phraseological reply known so far from phraseological research (Bondarenko [2009]; Khairov [2019]; Meterc & Pallay [2019]). The article analyzes modifications of the original (cinematic) situation and the puns associated with this phraseological reply in the internet memes. It also discusses the use of this reply in some scenes from series The Office [2005-2013], showing further propagation of this phraseme with new propagating agents.